GENEALOGICAL PERSPECTIVE OF THE LULUHYIA DIALECTS’ LEXICOSYNTACTIC SIMILARITIES - Lwangale, David Wafula; Bartoo, Dr. Phyllis J.; Mutiti, Prof. James K. (IJRDO- Journal of Educational Research, 2016)
The syntactic similarity of given languages may be used as evidence of their genealogicalrelatedness. This paper focuses on the lexicosyntactic similarities inherent across theLuluhyia dialects as evidence of their common origin. Despite the principle of languageuniversals as advanced by Naom Chomsky leading to universal grammar (UG), not alllanguages of the world ascribe to the same syntactic structure. The findings of the studypresented in this paper show that the Luluhyia dialects have the same syntactic structure as aresult of the similarities of their lexical items. Such syntactic similarities across the Luluhyiadialects are an indicator of a once linguistically and anthropologically unified communitywhose origin was undisputedly one. The Luluhyia dialects use basically the same words onlydiffering in pronunciation, stress placement and vowel length. In most cases, the distinctionbetween the Luluhyia dialects cannot be detected by non-native speakers of the dialects. Thevariations are mostly suprasegmental in nature. However, the relatedness of the Luluhyiadialects is overtly displayed prompting a genealogical connection